கொங்கு நாட்டின் இராசிபுர வட்டார சிறுதெய்வங்களும் வழிபாட்டு முறைகளும் / Deities and Worshipping Methods in the Rasipuram Region of Kongu Nadu - செ. தனபால் / S. Dhanapal (International Journal of Tamil Language and Literary Studies)
Man's early life was encircled by dangers for many thousands of years. Nature plays a major role in such risks. In the early times, nature seemed a mystery to man. The Sun, the Moon, darkness and deadly animals created fear in man. Fear becomes a mode of worship to worship nature. Natural death was very rare for them. They were led to destruction either by violence or illness before they reached old age. Early uncivilized men could not understand causal relationships. Then he modelled his physical activity and automatically taught a reason that there is a force within every natural object that is the cause of the action of objects. In early times, man worshipped nature as a goddess out of fear. Then, he gradually developed and worshipped it by giving it an image. He first worshipped idols under a tree. Then, he created a permanent abode for it. It was later called a temple. Nature worship, idol worship and polytheism were the basic reasons for the emergence of many temples in Tamil Nadu. The man who built the temples gradually developed the system of worship according to their clans. At first, he created the natural forces as deities and started worshipping them. Eventually, he created male and female deities and worshipped them by giving them an image and a name. He created and worshipped idols in the shape of mercy, anger, sitting and standing. The Tamil proverb 'Don't live in a place without a temple' (Kovil Illa Ooril Kudiyirukka Vendam) shows us that the people in every village build a temple and consider the temples are essential for wellbeing. Many temples are found in the southern part of Tamil Nadu based on this worship. Even today, the worship of minor deities is considered important among Tamils. Kongu region is one of the important regions that have lots of deity worship. Among the many areas, Rasipuram is a place that has lots of deities and worshipping cults. Hence, this article talks about the cults of minor deities in the Rasipuram region of the Kongu belt in Tamil Nadu.